The Guide Dog in Twenty-First-Century Representations of Disability: Reading Proposals and Their Adaptation for Polish Language Lessons - Miśkiewicz, Patrycja (Representations of Disability in Cultural Spaces, 2026)
In my article I address the role of dogs as guides, companions and therapists in literature aimed at young readers. The analysis is based on two selected works: Elcia and Dot. The mystery of the missing puppies by Megan Rix and Xirto, my mom’s guide dog by Katarzyna Śpiewak. In both works, four-legged friends play a significant role in the lives of people with disabilities, being not only a support to the heroines in their struggles with limitations, but also a source of love, joy and inspiration. The thesis discusses how children’s literature brings readers closer to the influence of animals on the lives of heroes, conveying basic values i.e. acceptance, compassion, respect, friendship and growing up. Character stories combined with a deep relationship with a guide dog break down stereotypes of disenfranchisement, teaching children to respond to the needs of others, fostering in them traits of sensitivity and empathy.